Increasing EFL Students’ Writing Skill Using Jigsaw and Online Searching Strategy - Yofita Christy Isgiarno; Bambang Yudi Cahyono; Hasti Rahmaningtyas (IJEE (Indonesian Journal of English Education), 2020)
ABSTRACTWriting is the practice of reaching out to one's mind and exploring it creatively. In writing activity, the writer should have accurate information, strong arguments, and good knowledge of organization and mechanics before delivering their ideas. However, in schools, writing is commonly considered as the most difficult skill to learn by the students of English as a foreign language (EFL). The problems of EFL students’ writing could refer to the five aspects of writing: content, organization, language use, vocabulary, and mechanics. This research aimed to increase the quality of the teaching and learning process in the classroom in order to improve EFL students’ writing skills by using the Jigsaw and Online Searching Strategy (JOSS). It used Action Research as the research design and was conducted in the tenth grade of Ilmu Bahasa dan Budaya (Language and Culture) class of Public Senior High School (SMA Negeri) 2 in Malang, East Java, Indonesia, which consisted of 22 students. The result showed that all of the students have passed the criteria of success and given good responses to the implementation of JOSS. Therefore, it is suggested that English teachers consider using JOSS as a teaching strategy to improve tenth-grade students’ writing skills.ABSTRAKMenulis merupakan aktivitas menjangkau pikiran seseorang dan menyampaikannya secara kreatif. Di dalam aktivitas menulis, penulis perlu mempunyai informasi yang akurat, argumen yang kuat, serta pengetahuan yang baik mengenai struktur teks dan mekanik dalam menulis sebelum menyampaikan ide-idenya. Namun, di sekolah-sekolah, menulis dipandang sebagai kemampuan yang paling sulit untuk dikuasai oleh para siswa yang mempelajari bahasa Inggris sebagai bahasa asing. Masalah dalam menulis dapat ditemukan dalam lima aspek tulisan yaitu isi, struktur teks, tata bahasa, kosakata, dan mekanik dalam menulis. Penelitian ini bertujuan untuk meningkatkan kualitas dalam proses pengajaran dan pembelajaran dalam kelas untuk meningkatkan kemampuan menulis siswa dalam belajar bahasa Inggris dengan menggunakan jigsaw dan pencarian informasi secara daring. Penelitian ini adalah Penelitian Tindakan. Penelitian ini dilakukan di SMA Negeri 2 Malang, Jawa Timur, Indonesia, pada kelas sepuluh Ilmu Bahasa dan Budaya yang terdiri atas 22 siswa. Hasil penelitian ini menunjukkan bahwa semua siswa telah mencapai kriteria kesuksesan dan memberikan respon yang baik mengenai penerapan strategi jigsaw dan pencarian informasi secara daring. Oleh sebab itu, guru bahasa Inggris disarankan untuk menggunakan strategi tersebut sebagai salah satu upaya untuk meningkatkan kemampuan menulis siswa kelas sepuluh. How to Cite: Isgiarno, Y. C., Cahyono, B.Y., Rahmaningtyas, H. (2020). Increasing EFL Students’ Writing Skill Using Jigsaw and Online Searching Strategy. IJEE (Indonesian Journal of English Education), 7(1), 95-108. doi:10.15408/ijee.v7i1.16383